Risk Factor for Retreatment Episode on Admission Among TB Patients With Schizophrenia - Wang, Hai-Rong; Han, Chao; Wang, Jun-Li; Zhang, Yan-An; Wang, Mao-Shui (Frontiers in Psychiatry, 2021)
Background The clinical characteristics of patients with tuberculosis (TB) and schizophrenia remain largely unknown. Furthermore, retreatment TB is associated with a poor outcome. Hence, we aimed to address the risk factors of retreatment TB in schizophrenia patients in this retrospective cohort. Methods Between March 2005 and August 2020, patients diagnosed with schizophrenia and TB were included in the study. Patient characteristics, such as demographics, medical history, underlying diseases, symptoms, outcome, and lab examinations, were collected from medical records using a structured questionnaire. TB retreatment was defined as treatment failures and relapses,. Subsequently, multivariate logistic regression was performed using variables selected based on prior findings as well as factors found to be associated with a retreatment episode in univariate analyses (P<0.1). Results A total of 113 TB patients with schizophrenia were included. Of them, 94 (83.2%) patients were classified as initial treatment group and 19 (16.8%) classified as retreatment group. The mean age was 53.0±23.2 years and males accounted for 61.9% of all cases. Multivariate analysis revealed that continuous antipsychotics treatment (OR=0.226, 95% CI: 0.074, 0.693; P=0.009) and extrapulmonary TB (OR=0.249, 95% CI: 0.080, 0.783; P=0.017) were associated with the retreatment in TB patients with schizophrenia. Conclusion Retreatment is a significant concern for TB patients with schizophrenia. To improve the current dilemma, continuous antipsychotics treatment is required and increasing awareness of schizophrenia would reduce the disease burden.